2017
DOI: 10.1002/cnma.201700344
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Characterization of Tb‐Doped Nanoferrites

Abstract: Tb3+‐substituted superparamagnetic iron‐oxide‐based nanoparticles (NPs) that can be promising for possible multimodal drug carrier and radiotherapy are presented. These NPs were obtained using a reverse micelle template method with controlled micelle size. The atomic ratio of Tb/Fe ions was found to be very close to that expected from the stoichiometry of the reagents used. Aqueous suspensions of Tb‐doped nanoferrites are emissive with emission peaks characteristic for the Tb3+ dopant. Time‐resolved fluorescen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…85–90 pm radius, and there is a large ionic radii mismatch for Ho 3+ (104 pm) as compared to Fe 3+ (78.5 pm) ions that are to be replaced in this lattice. However, the literature data [ 35 ] and our results for SPIONs modified with Tb (106 pm) [ 33 ] indicate that such replacement is possible, at least for terbium cations, requiring local lattice distortion and favouring incorporation of these ions into octahedral and surface sites. On the other hand, most ferrites are ferrimagnetic, i.e., part of magnetic moments of the constituent ions are antiparallel, partially compensating for the overall magnetic moment of SPIONs.…”
Section: Introductionmentioning
confidence: 64%
See 1 more Smart Citation
“…85–90 pm radius, and there is a large ionic radii mismatch for Ho 3+ (104 pm) as compared to Fe 3+ (78.5 pm) ions that are to be replaced in this lattice. However, the literature data [ 35 ] and our results for SPIONs modified with Tb (106 pm) [ 33 ] indicate that such replacement is possible, at least for terbium cations, requiring local lattice distortion and favouring incorporation of these ions into octahedral and surface sites. On the other hand, most ferrites are ferrimagnetic, i.e., part of magnetic moments of the constituent ions are antiparallel, partially compensating for the overall magnetic moment of SPIONs.…”
Section: Introductionmentioning
confidence: 64%
“…Substitution with ions with an ionic radius similar to Fe 3+ (0.785 Å) [ 31 ] does not affect the magnetic behaviour of the doped SPIONs significantly, while the incorporation of lanthanide ions like Ho 3+ (1.01 Å) [ 32 ] with a large radius, ca. 30% larger than Fe 3+ , may lead to core anisotropy, crystallographic lattice alterations and a decrease in the magnetic properties due to the Fe(III) and Ho(III) ionic radii mismatch [ 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition to cyclic and linear ligands like DOTA, HEHA or DTPA, they were various types of nanoparticles like gadolinium vanadate nanocrystals [16], polymersomes [17], indium and lanthanum phosphates [18,19]. In our work as a carrier for 225 Ac, we proposed to use Superparamagnetic Iron Oxide-based Nanoparticles (SPIONs) where actinium similarly to lanthanides should be incorporated into their magnetic core [20]. SPIONs have attracted wide attention due to their unique properties originating from intrinsic magnetic properties (due to ferromagnetic iron), high surface area-to-volume ratio, and the ability to chemically modify their core composition and their surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Combined with SEM images (see below), it could be observed that the incorporation of Tb 3+ /Gd 3+ had a great influence on the microstructure of Al 2 O 3 aerogel matrix. In addition, the doping of the sensitizing ion Gd 3+ did not change the crystal structure of Al 2 O 3 : Tb 3+ , suggesting that the ionic radius of Tb 3+ and Gd 3+ were similar, [24,25] and they occupied the crystal lattice site of Al 2 O 3 at the same time. These results indicated that the rare earth metal ions and the Al 2 O 3 aerogel matrix have strong binding force with Al 2 O 3 aerogel matrix, and the as‐prepared phosphor material had good physical and chemical stability.…”
Section: Resultsmentioning
confidence: 95%